The politics of change : explaining capital punishment reform in China - Miao, M (2014)
The thesis seeks to enhance understanding of the recent reform of capital punishment law, policies and institutions in China by studying its causes, significance, and limits. The research surveys the reform initiated by China’s top judiciary – the Supreme People’s Court - around 2006-2007. It demonstrates a changing domestic socio-political context, within which the external and internal impetus to reform is inevitable. Drawn from elite interview evidence with penal policy makers including judges, prosecutors, and legislators, the thesis concludes that Europe-inspired, cross-border abolitionist sentiments created motivation for change in China through soft mechanisms of shaming and persuasion, albeit to a limited degree. In the domestic realm, the research identified three pairs of interrelated tensions – the contradiction between elites and the public, the conflict between political intervention and judicial autonomy, and the divergent interests and priorities between top judicial organs and lower courts. These tensions are useful social, political and legal indicators to explain why and how China reformed its capital punishment machinery.